2023
DOI: 10.3390/life13071502
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Landscape of Immunotherapy in Uterine Cancer: A Comprehensive Review

Abstract: Endometrial cancer affects the uterus and is becoming increasingly common and deadly. Although surgery and adjuvant pelvic radiotherapy can often cure the disease when it is contained in the uterus, patients with metastatic or recurrent disease have limited response rates to chemotherapy, targeted agents, and hormonal therapy. To address this unmet clinical need, innovative treatment strategies are needed, and a growing focus on the immunomodulation of the tumor microenvironment has arisen. Current data sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In immunotherapies, an individual's own immune system is used to fight cancer, to pave the way for more specific and effective treatments. Immunotherapy use results in fewer side effects when compared to chemotherapy [33]. Two randomized clinical trials recently published in the New England Journal of Medicine (NEJM) found immunotherapy added to standard treatment for advanced and recurrent endometrial cancer in people with stage III and IV disease improves progression-free survival [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In immunotherapies, an individual's own immune system is used to fight cancer, to pave the way for more specific and effective treatments. Immunotherapy use results in fewer side effects when compared to chemotherapy [33]. Two randomized clinical trials recently published in the New England Journal of Medicine (NEJM) found immunotherapy added to standard treatment for advanced and recurrent endometrial cancer in people with stage III and IV disease improves progression-free survival [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Of the four TGCA molecular subtypes, the most common is the copy-number low subtype [ 22 ]. Its molecular characteristics include a relatively low mutational burden, characterized by fewer changes in the copy number variations throughout the genome and fewer deletions or duplications of large sections of DNA [ 22 , 47 ]. This results in more genome stability compared to the “copy-number high” subtype, which exhibits a higher number of these alterations.…”
Section: Molecular Subtypes Of Endometrial Cancermentioning
confidence: 99%
“…While the copy-number low subtype has lower mutational burden, they often carry specific mutations in genes that are known to be important in endometrial cancer pathogenesis. The most common mutations affect the PTEN gene, but mutations in other genes like PIK3CA, KRAS, and ARID1A are also frequently observed [ 47 ]. Of particular importance is the PI3K pathway, known to play an important role in genomic stability, cell cycle regulation and cell survival, resistance to chemotherapy, and DNA replication [ 48 ].…”
Section: Molecular Subtypes Of Endometrial Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This easy method is an effective therapy option, because these specific cells are able to recognize various tumor antigens rather than a single antigen [18] with a 40-50% response in patients with melanoma [19,20]. This method could be relevant in tumors where the presence of TILs has been established as a strong predictor of a favorable prognosis [21]. Currently, the practical perspective of TILs in different cancer types is promising for the use of monoclonal antibodies, such as antiprogrammed cell death (PD)-1 and anti-CD137 in the selection of T cells in TIL cultures with CD3+, helper, and cytotoxic T cell (CD4+ and CD8+ cells, respectively) as different fractions of TILs represented in the TME [22].…”
Section: Immunotherapy With Non-genetically Modified T Cellsmentioning
confidence: 99%